1979
DOI: 10.1055/s-0028-1096219
|View full text |Cite
|
Sign up to set email alerts
|

Thermocardiography – A Method for Continuous Assessment of Myocardial Perfusion Dynamics in the Exposed Animal and Human Heart

Abstract: In the exposed animal and human heart, coronary flow reduction results in a significant decrease of regional myocardial temperature. Epicardial temperature can be recorded instantaneously by the use of thermography. In contrast to other techniques, this method allows continuous assessment of rapid coronary flow changes and shows exactly the extent of myocardium involved. Value and limits of thermocardiography in animal experiments and during coronary bypass surgery are discussed and typical examples of myocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The data show that LAD bed temperature correlates linearly with coronary flow at flow rates below 100% setting results from the balance between (a) heat influx with coronary flow, metabolic heat production (which can be proportional to coronary flow), heat transfer from the ventricular blood through the LV thickness and (b) heat dissipation to the surrounding air through radiation and due to water evaporation. The coronary flow is considered to be a major contributor to the heat balance under normal conditions [5][6][7][8][9][10]. Indeed, early studies showed that in closed chest dogs the temperature of venous blood was ca.…”
Section: Epicardial Temperature and Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…The data show that LAD bed temperature correlates linearly with coronary flow at flow rates below 100% setting results from the balance between (a) heat influx with coronary flow, metabolic heat production (which can be proportional to coronary flow), heat transfer from the ventricular blood through the LV thickness and (b) heat dissipation to the surrounding air through radiation and due to water evaporation. The coronary flow is considered to be a major contributor to the heat balance under normal conditions [5][6][7][8][9][10]. Indeed, early studies showed that in closed chest dogs the temperature of venous blood was ca.…”
Section: Epicardial Temperature and Flowmentioning
confidence: 99%
“…However dependence on flow was linear only in the pathological range between 0% and 50% of baseline and leveled off at flows above 100% of normal. Yet another non-invasive technique that provides epicardial flow distribution in the exposed heart setting is infrared (IR) thermal imaging since the heart surface temperature is mainly determined by coronary flow [5][6][7][8][9][10]. However, application of thermal imaging, which yields 2-dimensional temperature maps of the cardiac surface, revealed non-linear dependence of DT on coronary flow at high flows [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…In horses, IRT has been applied for the diagnosis of lameness, back pain/intervertebral disk problem, muscle tears/strain, tendonitis, fractures, neuritis and peritonitis [9]. In dogs, infrared thermography has been experimentally introduced to detect the cardiac ischemia, coronary artery attenuation and intestinal infarction [1,2,4]. IRT was used for the determination of a dosage regimen of nimesulide, a cyclooxygenase 2 selective non steroidal antiinflammatory drug in the dog [8].…”
mentioning
confidence: 99%
“…In addition to ''static'' temperature maps, a temperature-jump technique has been used that is based on measurements of rates of temperature recovery following intracoronary injection of cold saline solution or its topical application (Robicsek et al 1978;Shabbo and Rees 1982). Despite a number of animal (Adachi et al 1987;Daniel et al 1979;Malm et al 1979;Papp et al 1985) and human (Daniel et al 1979;Robicsek et al 1978;Shabbo and Rees 1982) studies over the last 30 years, this method provided only qualitative information on the coronary flow deficits (Adachi et al 1987;Daniel et al 1979;Falk et al 1998;Gordon et al 1998;Malm et al 1979;Papp et al 1985;Robicsek et al 1978;Shabbo and Rees 1982). Recently, recovery kinetics after temperature jump was used to quantify coronary flow in isolated arrested pig hearts (Falk et al 1998) and dog hearts in vivo (Gordon et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Thermal imaging, which yields 2-dimensional temperature maps of the cardiac surface, is capable of detecting hypoperfused zones as the areas of reduced temperature because the heart surface temperature is mainly determined by coronary flow (Adachi et al 1987;Daniel et al 1979;Falk et al 1998;Gordon et al 1998;Malm et al 1979;Papp et al 1985;Robicsek et al 1978;Shabbo and Rees 1982). In addition to ''static'' temperature maps, a temperature-jump technique has been used that is based on measurements of rates of temperature recovery following intracoronary injection of cold saline solution or its topical application (Robicsek et al 1978;Shabbo and Rees 1982).…”
Section: Introductionmentioning
confidence: 99%